2020
DOI: 10.21037/atm.2020.02.100
|View full text |Cite
|
Sign up to set email alerts
|

GeneXpert® MTB/RIF assay with transbronchial lung cryobiopsy for Mycobacterium tuberculosis diagnosis

Abstract: Background: Early tuberculosis (TB) diagnostic is one of the critical steps to TB control. GeneXpert MTB/RIF has been widely proven for a prompt TB diagnosis. The use of GeneXpert MTB/RIF assay with transbronchial lung cryobiopsy samples may increase diagnostic accuracy. We aim to assess the diagnostic of TB with GeneXpert MTB/RIF assay with transbronchial lung cryobiopsy.Methods: Patients with suspected diagnosis of TB and negative smear microscopies, with TB culture and GeneXpert MTB/RIF assay with transbron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…UU.) (15). Hence, we might diagnose M. tuberculosis by a tissue culture; however, the final diagnosis was made on the basis of sputum culture results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UU.) (15). Hence, we might diagnose M. tuberculosis by a tissue culture; however, the final diagnosis was made on the basis of sputum culture results.…”
Section: Discussionmentioning
confidence: 99%
“…Since M. tuberculosis is not easily killed by cryopreservation ( 14 ), freezing with a cryoprobe is not expected to hinder tissue culturing. Additionally, it has been reported that the diagnostic rate of transbronchial cryobiopsy was 100% (16/16) by culture, while the rate was 81.3% (14/16) by GeneXpert Ⓡ MTB/RIF (Cepheid, Sunnyvale, USA) ( 15 ). Hence, we might diagnose M. tuberculosis by a tissue culture; however, the final diagnosis was made on the basis of sputum culture results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, Head et al technology has been widely adopted by clinical laboratories thereafter (16)(17)(18)(19)(20). A meta-analysis (including 15 studies) in 2014 showed that the overall sensitivity of DNA microarray for detecting RFP resistance was 0.91 (95% CI: 0.89-0.92), the overall specificity was 0.96 (95% CI: 0.96-0.97), and the AUC was 0.97 (21).…”
Section: Detection Of Rfp-resistant M Tuberculosis With Dna Microarraymentioning
confidence: 99%
“…We identified 50 articles: 17 [7,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] in the adult BAL group, 14 [35,[40][41][42][43][44][45][46][47][48][49][50][51][52] in the adult ES group, 7 [35,45,50,[53][54][55][56] in the adult IS group, 2 [57,58] in the pediatric ES group, 6 [57,[59][60][61][62][63] in the pediatric GA group, and 9 [59,[64][65][66][67]…”
Section: Studies' Characteristicsmentioning
confidence: 99%